In vitro evaluation of frictional resistance between ceramic brackets and orthodontic steel arches with and without glass coatings applied by sol-gel method - Rendón-Arias, Luz Adriana; Cano-Correa, Gustavo Adolfo; Peláez-Vargas, Alejandro; Jaramillo-Vallejo, Pedro M.; García-García, Claudia; Montoya-Góez, Yessid (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: to compare the in vitro static and dynamic frictional resistance between ceramic brackets and stainless steel wires with and without glass coatings applied by sol-gel method. Methods: 58 commercial stainless steel orthodontic wires AISI 304 (0.016 x 0.016 inch) were prepared with and without vitreous coating applied by Sol- Gel method. The in vitro static and dynamic frictional resistance of the wires on the mono-crystalline ceramic brackets were evaluated; also, the wire surfaces were characterized by means of Optical Microscopy and scanning electronic microscopy (SEM). Results: statistically significant differences were found between both groups under static (p = 0.000) as well as dynamic (p = 0.001) friction test. The friction values found in the coated group were higher (Static friction: 1.78 ± 0.44 N, Dynamic friction: 1.75 ± 0.49 N) than the group with no coating (Static friction: 1.37 ± 0.31 N, Dynamic friction: 1.41 ± 0.27 N). Characterization by SEM showed surface defects in both groups after the friction tests. Conclusion: the evaluated coatings did not perform better in terms of frictional behavior on sapphire mono-crystalline ceramic brackets when compared with the control group.